Characteristics of children and adolescents at the Switzerland-wide first ambulatory interdisciplinary pain clinic at the University Children’s Hospital Basel – a retrospective study (Swiss Medical Weekly, 2019)
AIMS OF THE STUDY Given the long history of underestimating chronic pain in children and adolescents, we lack valid data on its assessment and treatment. The psychological and economic burden for patients, their families and society is substantial. The aim of this study was to assess patient characteristics of the first ambulatory interdisciplinary clinic for children and adolescents with chronic pain in Switzerland and compare them with data from other international centres. METHODS All patients of the ambulatory interdisciplinary pain clinic at the University Children’s Hospital in Basel during the period from 4 January 2012 to 4 July 2016 were included in this retrospective study. Data were collected from the patients’ medical records and from a questionnaire, which the patients and their parents received and completed in advance of their first visit. Demographic information, pain, referral, social environment, therapies and school absences of the patients were statistically analysed with means, percentages, 95% confidence intervals (CIs) and standard deviations (SDs). RESULTS Of the 135 patients included in this study, 80% were female and the mean age of all patients was 13.95 years (95% CI 13.5–14.4). The commonest pain presentations were: musculoskeletal (38%, 95% CI 0.30–0.46), back (25%, 95% CI 0.18–0.33), multiple regions (21%, 95% CI 0.15–0.28) and headache (7%, 95% CI 0.03–0.12). Mean duration of pain until the patients came to the clinic was 24.5 months (95% CI 19.82–29.22). Physiotherapy (71%, 95% CI 0.63–0.79) and non-opioids (50%, 95% CI 0.42–0.59) were the most used therapies before the first meeting. Psychotherapy (52%, 95% CI 0.44–0.61), most often using a psychosomatic therapeutic approach (psychosomatic therapy) 34% (95% CI 0.26–0.42), physiotherapy (36%, 95% CI 0.27–0.44) and non-opioids (33%, 95% CI 0.25–0.42) afterwards. The mean number of school absences during the last month before the first visit was 5.1 days per month (95% CI 3.48–6.73). The parents of our study participants suffered more often from psychiatric diseases than the mean Swiss population. CONCLUSIONS The average of more than 2 years of pain before referral to the clinic seems to be a long time. Assuming that specialised support is mandatory for young patients with complex pain syndromes, the referral time should be reduced. Furthermore, patients with headache were underrepresented in Basel compared with other centres. Interestingly, in our study, patients’ parents suffered more often from psychiatric diseases than the mean Swiss population.